Adjusting the LTE structural design to 5G: prospects and challenges - Alam, Md Shamsul; Rahman, Md. Mirazur; Samy, Md. Arif Abdulla; Afroj, Jinia; Prottasha, Soheli Noshin; Uddin, Md. Nasir; Ahammed, Samrat; Rashid, Muhammad Mahbubur (The Mattingley Publishing Co., Inc., 2020)
Research directions indicate a behemoth shift will be required from the existing framework to activate 5G in full swing. Current researches are intensively working in this field, however, it will take significant time to reach the ultimate goal. Emphasis has been given on the factors and challenges of 5G, solutions have been proposed accordingly, and some ideas about the architecture have been achieved so far. The work shown in this study is not necessarily a radical one, rather demonstrated the challenges, their possible solutions, and more importantly the proposed solutions are precisely discussed in the context of the architecture. It has been assumed that the whole architecture is closely adjacent to the existing 4G architecture, except that all those elements in the same architecture will be far more capable to enable 5G. Addressing the requirements in a very precise approach, addressing the solutions, and finally locating exactly where they would be applied within the architecture is the main objective.